Clinical management of sepsis-associated acute respiratory distress syndrome: current evidence and future directions - Liu, Liang; Wu, Linguangjin; Chen, Ying; Deng, Rou; Hu, Yingying; Tu, Yanjie; Fang, Bangjiang (Frontiers in Medicine, 2025)
Sepsis is a life-threatening condition characterized by organ dysfunction resulting from a dysregulated host response to infection. The lungs are among the first and most significantly affected organs in sepsis. Pulmonary infections or systemic inflammatory cascades triggered by various pathogens can lead to acute and diffuse pulmonary damage, often manifesting as persistent hypoxemia. The COVID-19 pandemic has highlighted critical knowledge gaps in SA-ARDS management, necessitating paradigm reevaluation under the new global definition of ARDS. This paper analyzes the pathomechanisms and subphenotype characteristics of SA-ARDS, reviews recent advances in clinical management, such as fluid resuscitation, antimicrobial therapy, immune modulation, respiratory support, microcirculatory improvement, and traditional Chinese medicine (TCM) therapies, and addresses controversial issues and areas requiring further investigation.